The Effect of Good Corporate Governance, Profitability, and Leverage on Firm Value (A Study of Property and Real Estate Companies Listed on the Indonesia Stock Exchange During the 2020–2024 Period) - Avika Nur Hanifah; Bagus Hari Sugiharto (Universitas Ibn Khladun Bogor, 2026)
Firm value reflects a company’s ability to create shareholder wealth and attract investors. This study examines the effects of Good Corporate Governance (GCG), profitability, and leverage on firm value in Property and Real Estate companies listed on the Indonesia Stock Exchange during 2020–2024. GCG is measured by the proportion of independent commissioners, profitability by Return on Assets (ROA), leverage by Debt to Equity Ratio (DER), and firm value by Price to Book Value (PBV). This research employs a quantitative explanatory approach using secondary data from annual reports and audited financial statements. Purposive sampling produced 120 firm-year observations, which were analyzed using multiple linear regression with SPSS. The findings reveal that GCG, profitability, and leverage simultaneously have a significant effect on firm value. Individually, each variable also exerts a positive and significant influence. These results indicate that effective corporate governance, strong profitability, and appropriate leverage management contribute to enhancing firm value and strengthening investor confidence.